Political Ecology of Environmental Conflict in the Tumpang Pitu Gold Mining, Indonesia - Muhammad Rafael; Muhammad Rizki; Abiyyu Imamul; Rafli Muhammad; Iradhad Taqwa Sihidi (Internasional Journal of Politics and Public Policy, 2026)
This study examines environmental conflict surrounding the Tumpang Pitu gold mine in Banyuwangi through a Political Ecology perspective. The conflict, ongoing since the start of mining operations, reflects not merely technical environmental impacts but unequal power relations among the state, corporations, and local communities. Using a qualitative document-based approach, data were drawn from government policies, Environmental Impact Assessment (EIA) documents, civil society reports, media coverage, and relevant academic literature. Thematic analysis was applied, employing the Environmental Justice framework to assess distributive injustice, procedural exclusion, and the lack of recognition of affected communities’ rights. Findings show that mining governance prioritized economic growth and investment security, while ecological sustainability and meaningful public participation were marginalized. Licensing and EIA processes were largely formalistic, restricting community involvement and overlooking ecological risks to coastal ecosystems and local livelihoods.